2010
DOI: 10.1172/jci38331
|View full text |Cite
|
Sign up to set email alerts
|

Myc controls transcriptional regulation of cardiac metabolism and mitochondrial biogenesis in response to pathological stress in mice

Abstract: In the adult heart, regulation of fatty acid oxidation and mitochondrial genes is controlled by the PPARγ coactivator-1 (PGC-1) family of transcriptional coactivators. However, in response to pathological stressors such as hemodynamic load or ischemia, cardiac myocytes downregulate PGC-1 activity and fatty acid oxidation genes in preference for glucose metabolism pathways. Interestingly, despite the reduced PGC-1 activity, these pathological stressors are associated with mitochondrial biogenesis, at least init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(143 citation statements)
references
References 80 publications
6
133
1
2
Order By: Relevance
“…Most of the studies on c-Myc-transcribed genes are in the context of cancer, although some studies have clearly demonstrated its overexpression following injury (51). Although cancer and injury may share certain biological characteristics such as hypoxia and inflammation, the regulation of genes following injury is expected to have a different signature; the c-Mycmodulated spectrum of genes has not been clearly defined (38,48,52).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies on c-Myc-transcribed genes are in the context of cancer, although some studies have clearly demonstrated its overexpression following injury (51). Although cancer and injury may share certain biological characteristics such as hypoxia and inflammation, the regulation of genes following injury is expected to have a different signature; the c-Mycmodulated spectrum of genes has not been clearly defined (38,48,52).…”
Section: Discussionmentioning
confidence: 99%
“…HIF and c-Myc act on multiple targets to regulate carbon metabolism and act in concert to fine tune adaptive responses to hypoxic environment (52). In pathological stress, c-Myc regulates the increased metabolic energy demand, then mitochondrial biogenesis (45). Additionally, the c-Myc protein level has been shown to increase markedly after hypoxia and ischemia (53).…”
Section: Discussionmentioning
confidence: 99%
“…These changes are associated with diminution of Ppargc1a and Esrra expression (31,32). The signals leading to their down-regulation during heart failure are still elusive (33), although MYC has been proposed as a potential upstream repressor of Ppargc1a transcription (34).…”
Section: Dissection Of Moribund Med30mentioning
confidence: 99%